Pelaksanaan Program Cygos (Cyber Government Semarang) Sebagai Penunjang Pelayanan Publik di Kota Semarang - Firmansah, Ardhi (Unnes Political Science Journal, 2017)
Currently the technology has developed rapidly, especially internet access technology. Semarang City Government to respond to input from the community and then create a program Cyber Government Semarang to reach the needs of the community in the form of information and administrative services. The purpose of this study are: to describe the implementation of the program CyGoS as supporting public service with reference to the theory of EGovernment implementation by Sharon S.Dawes, describes a model of political communication Semarang government in implementation CyGoS terms of political communication theory, analyzing the perception of the public about the program CyGoS use the theory of public service Groonroos. Results from this study that uses qualitative methodology to conduct research observation section PDE (Electronic Data Processing) Semarang government and conducted interviews to Dr.Ir.NanaStorada, SE.MM as Head. PDE generate some information that answers the following research: a description of the program, carried out political communication and public perception regarding the program. Expected results of this study can serve as a reference as an evaluation of the government for public services based on information technology and communications in the city of Semarang optimized so as to create good public service in Semarang City Government.